“Distracters” Do Not Always Distract: Visual Working Memory for Angry Faces is Enhanced by Incidental Emotional Words - Jackson, Margaret C.; Linden, David E.; Raymond, Jane E. (Frontiers in Psychology, 2012)
We are often required to filter out distraction in order to focus on a primary task during which working memory (WM) is engaged. Previous research has shown that negative versus neutral distracters presented during a visual WM maintenance period significantly impair memory for neutral information. However, the contents of WM are often also emotional in nature. The question we address here is how incidental information might impact upon visual WM when both this and the memory items contain emotional information. We presented emotional versus neutral words during the maintenance interval of an emotional visual WM faces task. Participants encoded two angry or happy faces into WM, and several seconds into a 9 s maintenance period a negative, positive, or neutral word was flashed on the screen three times. A single neutral test face was presented for retrieval with a face identity that was either present or absent in the preceding study array. WM for angry face identities was significantly better when an emotional (negative or positive) versus neutral (or no) word was presented. In contrast, WM for happy face identities was not significantly affected by word valence. These findings suggest that the presence of emotion within an intervening stimulus boosts the emotional value of threat-related information maintained in visual WM and thus improves performance. In addition, we show that incidental events that are emotional in nature do not always distract from an ongoing WM task.